2007
DOI: 10.1212/01.wnl.0000265517.66976.28
|View full text |Cite|
|
Sign up to set email alerts
|

Practice Parameter: Treatment of nervous system Lyme disease (an evidence-based review): Report of the Quality Standards Subcommittee of the American Academy of Neurology [RETIRED]

Abstract: Objective: To provide evidence-based recommendations on the treatment of nervous system Lyme disease and post-Lyme syndrome. Three questions were addressed: 1) Which antimicrobial agents are effective? 2) Are different regimens preferred for different manifestations of nervous system Lyme disease? 3) What duration of therapy is needed? Methods: The authors analyzed published studies ) using a structured review process to classify the evidence related to the questions posed. Results: The panel reviewed 353 abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
142
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(159 citation statements)
references
References 63 publications
2
142
0
11
Order By: Relevance
“…13 Where there is encephalo myelitis there are insufficient data to indicate that oral therapy is not inferior and therefore an intravenous regimen is preferred (see Table 2). 14,15 The outcome following treatment is variable with age, duration of symptoms and severity of meningeal inflammation all influencing recovery. Follow-up of 102 appropriately treated patients in Norway found that 70 per cent had complete resolution of signs four months after treatment, with the remainder showing improvement.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…13 Where there is encephalo myelitis there are insufficient data to indicate that oral therapy is not inferior and therefore an intravenous regimen is preferred (see Table 2). 14,15 The outcome following treatment is variable with age, duration of symptoms and severity of meningeal inflammation all influencing recovery. Follow-up of 102 appropriately treated patients in Norway found that 70 per cent had complete resolution of signs four months after treatment, with the remainder showing improvement.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…Additionally, all indicated known diagnostic workup regarding neuroborreliosis has to be negative. [1,2] A sufficient amount of data shows that patients with PTLDS have reduced life functioning than those without the syndrome, [3] or even when compared to patients with other chronic diseases. [4] Intuitively, the presence of PTLDS after recommended treatment is associated with significantly increased health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Some already treated patients rarely develop a facial nerve palsy or meningitis. [1,2,6] Cranial neuritis, in most cases, appears to be benign, and it is attributed not to a persistent infection but to residual, irreversible neurologic damage. Conversely, if Lyme meningitis was developed shortly after the completion of a course of oral antimicrobial therapy, the patient undergoes another cycle of treatment with either ceftriaxone or with a similar parenteral antibiotic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations